Perlindungan Hukum Terhadap Pemegang Sertifikat Hak Milik Dalam Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum - Simamora, Van Basten; Pietersz, Jemmy Jefry; Uktolseja, Novyta (Faculty of Law Universitas Pattimura, 2025)
Land procurement is the process of providing land for development purposes by offering fair and just compensation to the entitled parties. The land acquisition process is carried out through the relinquishment of rights by the landowner to the institution that requires the land. In an effort to ensure land availability, the government often has to take land from the community for the smooth progress of development for the public good. This is due to the limited land owned by the government, but in its implementation, such actions should not harm the landowners. Therefore, the government is obliged to provide appropriate and fair compensation, so as to support the improvement of the community's quality of life. The purpose of this research is to evaluate and analyze the legal protection provided to certificate holders related to land acquisition conducted by the government for public interest. The method used in this research is normative juridical with a descriptive-analytical research type, relying on primary, secondary, and tertiary legal sources. The analysis of legal materials is conducted using appropriate analytical methods. The results of the research on legal protection for certificate holders of ownership rights in land acquisition for development aimed at public interest show that the regulations and legal protection related to compensation for land rights holders are governed by Article 33 paragraph 1 of the 1945 Constitution, Article 24H paragraph 4 of the 1945 Constitution, the Basic Agrarian Law No. 5 of 1960, and Law No. 2 of 2012 on Land Acquisition. If an agreement on compensation cannot be reached between the landowner and the party requiring the land, the compensation will be deposited in the local district court through a judicial process known as consignment. In the implementation of consignment, it is important to prioritize the Principle of Caution and the Principle of Respect for the Rights of Former Land Rights Holders in accordance with Presidential Regulation Number 39 of 2023, which amends Government Regulation Number 19 of 2021 concerning the Implementation of Land Acquisition for Public Interest.